Blood Glucose Lowering Effect of Ficus deltoidea Aqueous Extract - Aminudin, Norhaniza; Y.S, Chung; E.S, Chee; I.N, Kang; R, Lee (Malaysian Journal of Science, 2007)
Ficus deltoidea has traditionally been used to cure several pathological conditions including diabetes. However, none of these claims have been scientifically researched thus far. In this preliminary study, the blood glucose lowering activity of F. deltoidea was monitored through the oral glucose tolerance test. Post-treatment of the aqueous extracts of both the leaves and fruits of F. deltoidea at 50mg/kg dosage significantly reduced the external glucose load. Both extracts were found to be non-toxic as shown by the brine shrimp toxicity test.